A HISTÓRIA DE META-HISTÓRIA: Um estudo sobre a teoria de Hayden White - RIZZO, Marcelo Augusto Parrillo (2009)
This work concerns to Hayden White´s conception of history, like was exposed in his book Metahistory and the compilations of his articles. It will be presented and discussed White´s interpretation about the relation of the historical discipline with literature and science, Relation that guides his understanding of historical writing.